Estrategias de enunciación política y posicionamiento del estado en el contexto internacional:: el discurso de Evo Morales en la cumbre de cambio climático de Copenhague (2009) - Fernández, María del Rosario (Papeles de Trabajo. Centro de Estudios Interdisciplinarios en Etnolingüística y Antropología Socio-Cultural, 2020)
The speech analyzed here we were interested in extending a planetary level, the concept of territoriality, which allows strengthen the political position of the bolivian state. The study is framed in the analysis of the speech, focusing, first, in the discrimination of the big scenes (Maingueneau, 2004) and, especially, in the characterization of the political sentences (Lozano Cividano, 2007).